Strategic Transfers for the Education Inspectorate from Erasmus+ Mobility: The Bavarian Model - Ortiz Ballester, Elena; Sempere Espí, Soledad (Avances en Supervisión Educativa, 2026)
This article analyses the professional transfers derived from an Erasmus+ KA1 mobility carried out in Bamberg (Bavaria, Germany) from 20 to 24 October 2025 by three Spanish education inspectors. The aim is to identify relevant lessons from the Bavarian education system—regarding school autonomy, shared leadership, external evaluation, teacher training and dual vocational education—and assess their transferability to the Spanish inspection model and school leadership practices. The methodology was qualitative, based on direct observation, structured interviews and documentary analysis during visits to educational institutions and authorities. Findings reveal a system characterised by strong institutional autonomy, collaborative professional culture and standards-based evaluation. It is concluded that Erasmus+ mobility represents a strategic opportunity to strengthen the European dimension of educational inspection, promote evidence-based practices and enrich advisory and supervisory functions.